2020
DOI: 10.1016/j.phrs.2019.104589
|View full text |Cite
|
Sign up to set email alerts
|

Exploring mechanisms of increased cardiovascular disease risk with antipsychotic medications: Risperidone alters the cardiac proteomic signature in mice

Abstract: Atypical antipsychotic (AA) medications including risperidone (RIS) and olanzapine (OLAN) are FDA approved for the treatment of psychiatric disorders including schizophrenia, bipolar disorder and depression. Clinical side effects of AA medications include obesity, insulin resistance, dyslipidemia, hypertension and increased cardiovascular disease risk. Despite the known pharmacology of these AA medications, however, the mechanisms contributing to adverse metabolic side-effects are not well understood. To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 105 publications
(151 reference statements)
1
39
1
Order By: Relevance
“…Similarly, significantly depressed levels of cytochrome oxidase subunit VI B (COX6B) during both RIS and OLAN treatment would lead to profound changes in oxidative phosphorylation and metabolic rate that may not be reflected as level changes of downstream proteins because differentially phosphorylated states are not detected. However, metabolic changes in AA-treated patients and our previous report phenotypically demonstrate mitochondrial dysfunction that is highly consistent with reduced oxidative phosphorylation [21]. Finally, DE by both RIS and OLAN of proteins whose function depends on their phosphorylation state are highly likely to be relevant in the absence of posttranslational modification detection when the predicted phenotype is consistent with known AA-induced side effects.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Similarly, significantly depressed levels of cytochrome oxidase subunit VI B (COX6B) during both RIS and OLAN treatment would lead to profound changes in oxidative phosphorylation and metabolic rate that may not be reflected as level changes of downstream proteins because differentially phosphorylated states are not detected. However, metabolic changes in AA-treated patients and our previous report phenotypically demonstrate mitochondrial dysfunction that is highly consistent with reduced oxidative phosphorylation [21]. Finally, DE by both RIS and OLAN of proteins whose function depends on their phosphorylation state are highly likely to be relevant in the absence of posttranslational modification detection when the predicted phenotype is consistent with known AA-induced side effects.…”
Section: Discussionsupporting
confidence: 75%
“…All animals used in this study were healthy and displayed no adverse effects of daily gavage for the 28-day study duration. Details of animal growth rates, locomotor activity, adiposity, and energy expenditure for this cohort were recently reported in a manuscript describing AA effects on the heart [ 21 ]. Overall, the animals in this study showed normal feeding behavior, weight gain, and locomotor activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The groups were subsequently separated to form two subgroups: one receiving 1 mg/kg oral risperidone (Sigma-Aldrich, St. Louis, MO, USA) and the other (control group) receiving saline through daily gavage for the final 56 days of the diet period (36.71 ± 0.69 g in risperidone-treated mice and 36.69 ± 0.61 g in control mice (vehicle treated), p > 0.05). Literature on risperidone as a potential drug for application, in studies on behavior, antipsychotic disease, immunosuppression, and cardiovascular disease in a mouse model was referenced when selecting the risperidone dose [ 68 , 69 , 70 ]. During the study, mice were separately kept in microisolation cages placed on racks ventilated by air filtered by high-efficiency particulate air filters under temperature and humidity controlled at 22 ± 1 °C and 55% ± 5%, respectively, under a 12:12-h light/dark cycle, all with free water and food access.…”
Section: Methodsmentioning
confidence: 99%